2015
DOI: 10.18632/oncotarget.4824
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptomics-based identification of cryptic drivers of taxol-resistance genes in ovarian carcinoma cells: Analysis of the androgen receptor

Abstract: A systematic analysis of the genes involved in taxol resistance (txr) has never been performed. In the present study, we created txr ovarian carcinoma cell lines to identify the genes involved in chemoresistance. Transcriptome analysis revealed 1,194 overexpressed genes in txr cells. Among the upregulated genes, more than 12 cryptic transcription factors were identified using MetaCore analysis (including AR, C/EBPβ, ERα, HNF4α, c-Jun/AP-1, c-Myc, and SP-1). Notably, individual silencing of these transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 39 publications
7
37
0
Order By: Relevance
“…Moreover, ectopic expression of AR by AR plasmid in AR‐null HEK293 cells induced resistance to taxol by 1.8‐fold (Figure f). This observation is consistent with previous findings showing that AR expression and nuclear location affect taxol sensitivity in early stage of acquired txr (N. K. Sun et al, ). Similarly, ABCB1 mRNA level was also induced by taxol in HEK293 following transfection with AR complementary DNA (Figure g).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, ectopic expression of AR by AR plasmid in AR‐null HEK293 cells induced resistance to taxol by 1.8‐fold (Figure f). This observation is consistent with previous findings showing that AR expression and nuclear location affect taxol sensitivity in early stage of acquired txr (N. K. Sun et al, ). Similarly, ABCB1 mRNA level was also induced by taxol in HEK293 following transfection with AR complementary DNA (Figure g).…”
Section: Resultssupporting
confidence: 94%
“…Taxol‐induced ABCB1 expression and chromatin modification was dramatically suppressed by the AKT inhibitor, but not by the other kinase inhibitors tested (Figure a). AR expression is dependent on AKT and JNK pathways in these cells as only AKT and JNK inhibitors (Wortmannin and SP600125, respectively) downregulated AR expression (N. K. Sun et al, ). These results suggest that the AKT pathway likely represents a target of sub‐lethal taxol treatment in upregulating ABCB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how CAV-1 reduces Taxol resistance and autophagy, the role of JNKs in this process was analyzed as JNKs have previously been reported to mediate Taxol resistance in ovarian carcinoma cells (19), and JNK1-mediated phosphorylation of B cell lymphoma-2 has an important role in the regulation of autophagy (20). To compare Taxol-resistant cells and their parent cells, the activation of the phosphorylation of JNK and upstream Akt was increased, suggesting an increase in JNK activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factor AP-1 is mainly composed of Jun (c-Jun, JunB, and JunD) and Fos (c-Fos, FosB, Fra-1, and Fra-2) (20,21). Previous study showed that AP-1 is required for cell survival and involved in multidrug resistance (22,23). In this study, using ChIP and dual luciferase reporter assay, we show for the first time that c-Jun/c-Fos can directly bind to the ID1 promoter, thereby activating ID1 transcription and expression in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 is a mammalian transcription factor and collectively describes a group of structurally and functionally related members of the Jun protein family (c-Jun, JunB, and JunD) and Fos protein family (c-Fos, FosB, Fra-1, and Fra-2) (20,21). It has been reported that AP-1 is required for cell survival and involved in multidrug resistance (22,23). Recent research demonstrated that the aberrantly high levels of ID1 expression in cancer are often a consequence of transcriptional induction by many proteins that are activated in a constitutive manner in cancer cells and affect chemoresistance (24 -26).…”
mentioning
confidence: 99%